LIN, a Medicago truncatula Gene Required for Nodule Differentiation and Persistence of Rhizobial Infections - Kuppusamy, Kavitha T. (American Society of Plant Biologists, 2004)
Ethyl methanesulfonate mutagenesis of the model legume Medicago truncatula has previously identified several genes required for early steps in nodulation. Here, we describe a new mutant that is defective in intermediate steps of nodule differentiation. The lin (lumpy infections) mutant is characterized by a 4-fold reduction in the number of infections, all of which arrest in the root epidermis, and by nodule primordia that initiate normally but fail to mature. Genetic analyses indicate that the symbiotic phenotype is conferred by a single gene that maps to the lower arm of linkage group 1. Transcriptional markers for early Nod factor responses (RIP1 and ENOD40) are induced in lin, as is another early nodulin, ENOD20, a gene expressed during the differentiation of nodule primordia. By contrast, other markers correlated with primordium differentiation (CCS52A), infection progression (MtN6), or nodule morphogenesis (ENOD2 and ENOD8) show reduced or no induction in homozygous lin individuals. Taken together, these results suggest that LIN functions in maintenance of rhizobial infections and differentiation of nodules from nodule primordia.